Correction: Selective photocatalysis of lignin-inspired chemicals by integrating hybrid nanocatalysis in microfluidic reactors. (2nd November 2017) - Colmenares, Juan Carlos; Varma, Rajender S.; Nair, Vaishakh
Abstract : Correction for 'Selective photocatalysis of lignin-inspired chemicals by integrating hybrid nanocatalysis in microfluidic reactors' by Juan Carlos Colmenares et al., Chem. Soc. Rev., 2017, DOI: ; Web:10.1039/c7cs00257b .